Movements and Meanings: Towards an Integrated Approach to Political Discourse Analysis - Ponton, D.M. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2016)
This chapter has two principal focuses; firstly backwards in time, across some of the high points in the development of political discourse analysis, in order to assess the current state of the field. It also has a future focus, as it attempts to integrate insights from some emerging fields, such as Multimodality, with more consolidated approaches. It has been argued, in many accounts (e.g. Fairclough and Fairclough 2012), that persuasion is the most pervasive function of all political discourse, and most authors agree that the processes involved encompass both textual and non-textual features. An influential early attempt, for example, to describe some non-verbal aspects of persuasive rhetoric was Atkinson (1984), who identified features like the speaker’s voice quality, intonation, posture, body language, eye movements, and so on, as well as some other non-linguistic ‘tricks’. As influential as this work was, however, these features have tended to be omitted from many subsequent accounts of persuasion in political rhetoric, which have concentrated on features of argumentation operating at a strictly textual level.The overall aim of this work is to suggest pathways towards the ambitious goal of developing a usable, integrated model for analysing political discourse. Instead of analysing a single feature such as metaphor (Charteris-Black 2006), parliamentary insults (Ilie 2004), evaluative language or humour (Swain 1999, 2002), the model attempts to combine descriptions of textual and non-verbal/multimodal features of political discourse, in order to provide a practical tool for analytical purposes, and a coherent account of their possible pragmatic effects.